PRINCIPAL'S MANAGERIAL COMPETENCE IN DEVELOPING RELIGIOUS CULTURE IN SMP 19 N MERANGIN DISTRICT, JAMBI PROVINCE - Desmiati; Kusnadi, Edy; Yunus , Abdullah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Managerial competence for school principals is one of the basic principles in managing educational institutions and developing a religious culture in schools. One of the backgrounds of this research is that the religious culture at SMP N 19 Merangin has become a real practice and a shared vision in educational institutions. This research was conducted using qualitative methods. Data sources were obtained through observation, interviews, and documentation. Data analysis was carried out using data reduction techniques, data presentation, and data verification. The result of this study is that the principal's managerial competence in developing a religious culture by emphasizing and managing resources at SMP N 19 Merangin. These resources are encouraged by planning and implementation by teachers and students as well as adequate learning facilities. Such as disciplinary attitudes, religious literature, and environmental support in the development of a religious culture. In addition, the development of a religious culture is practiced in the rules or regulations of students in the school environment, such as respecting religious differences, differences of opinion, and religious celebrations. The practice has become a living value that takes place in the daily lives of school members.